ANALISIS INTERNALISASI NILAI-NILAI PHBS PADA ANAK PANTI ASUHAN AISYIYAH TUNAS HARAPAN PONTIANAK - Dina, Afra Ayu; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe title of these research was â€œThe Internalization of analysis of clean and healty living behavior values in the children of Panti Asuhan Aisyiyah Tunas Harapan Pontianak. The general problem in this research is the internalization process about clean and healty living behavior values in children of Panti Asuhan Aisyiyah Tunas Harapan Pontianak. The purposes in this research is to know the internalization process about clean and healty living behavior values in term of exemplary, habituation, dan socialization aspects. The approach in this research is qualitative approach and descriptive method. The technique of data collection in this research is passive pasrticipation observation, interviews, and documentary studie. The tools of this research is in the form of observation guides, interview guides, field notes, and camera. The technique of data analysis is data reduction, data presentation and conclusion retraction. The alaysis in this research presented descriptively by using 5 informants consist of Mr. RB the caretaker of the Panti Asuhan Aisyiyah Tunas Harapan Pontianak and YN, SN, AN, and DN as the children of the Panti Asuhan Aisyiyah Tunas Harapan Pontianak. The results from this research indicate that the internalization process about clean and healty living behavior valeus in children of Panti Asuhan Aisyiyah Tunas Harapan Pontianak form the caretaker of the Panti Asuhan is already done. This is proven in examples and socialization from the 6 indicators PHBS that is 1) using the clean water 2) wash their hands with clean water and soap 3) use healty latrines 4) eradicate mosquito larvae 5) eat the vegetables and fruits 6) doing some physical activity. While in the aspect of habituation, children of the Panti already done clean and healty life behavior in their daily lives.Â Keywords: Internalization, Values, PHBS Â